2008
DOI: 10.1124/jpet.108.141713
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Methylphenidate on Knockin Mice with a Methylphenidate-Resistant Dopamine Transporter

Abstract: Methylphenidate (Ritalin) is one of the most commonly abused prescription drugs. It is a psychostimulant that inhibits the dopamine and norepinephrine transporters with high affinity. In mice, methylphenidate stimulates locomotor activity, is selfadministered, and produces conditioned place preference, typical properties of an addictive drug. We have generated a knockin mouse line bearing a mutant dopamine transporter that is approximately 80-fold less sensitive to cocaine inhibition than wild type. It is inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
(42 reference statements)
1
29
0
1
Order By: Relevance
“…We also observed that pharmacological enhancement of 5HT transmission did not alter P-Thr202/ Tyr204-ERK42/44 levels in DAT-CI striata. Consistent with previous data (Tilley and Gu, 2008b), we also found that a selective NET blocker, nisoxetine, through enhancement of NA transmission, attenuated the motor hyperactivity of DAT-CI mice. However, this effect results to be moderate, if compared with the strong motor sedation induced by amphetamine, nomifensine, and bupropion.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We also observed that pharmacological enhancement of 5HT transmission did not alter P-Thr202/ Tyr204-ERK42/44 levels in DAT-CI striata. Consistent with previous data (Tilley and Gu, 2008b), we also found that a selective NET blocker, nisoxetine, through enhancement of NA transmission, attenuated the motor hyperactivity of DAT-CI mice. However, this effect results to be moderate, if compared with the strong motor sedation induced by amphetamine, nomifensine, and bupropion.…”
Section: Discussionsupporting
confidence: 81%
“…Consistently, DAT-KO mice have been considered a reliable animal model for this psychiatric disorder (Giros et al, 1996;Gainetdinov et al, 1999a;Gainetdinov, 2008). Recent studies have revealed that DAT-CI mutants with three point mutations in the cocaine binding site of the DAT gene show increased basal motor activity, absence of cocaineinduced extracellular DA elevation, and loss of cocaine-and methylphenidate-induced conditioned place preference (Chen et al, 2006;Tilley and Gu, 2008b). In this work, we further confirm that DAT-CI mutants show basal horizontal and vertical hyperactivity, accompanied by a mild reduction of cognitive ability, whereas no alterations were observed in motor coordination.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has also been shown that stereotypy was not seen with methylphenidate in dopamine depleted animals or knocked in mice. 22 Hence, on the above grounds, we recommend that methylphenidate can be used and further established as an alternative model for inducing psychosis in animals for evaluation of newer typical antipsychotics which work mainly through dopamine pathways.…”
Section: Methylphenidate As a Model For Psychosis (Stereotypy)mentioning
confidence: 99%
“…14 Perhaps the most clear-cut data without such a developmental confound come from a knock-in mouse expressing a functional DAT mutant that transports DA at wild-type levels but has a greatly reduced affinity for cocaine 17 and MPH. 18 This mouse shows significantly reduced hyperlocomotion in response to cocaine and MPH, as well as impaired cocaine selfadministration 19 and conditioned place preference 17,18 , measures of drug-induced reward. These studies indicate that DAT is indeed the essential target for the rewarding properties of cocaine and MPH.…”
mentioning
confidence: 99%